Comparison of hybrid maize (Zea mays L.) performance developed through conventional pedigree and doubled haploid breeding methods - Aleri, Isaiah; Beyene, Yoseph; Chavangi, Andrew; Gowda, Manje; Burgueño, Juan; Chaikam, Vijay (Wiley, 2025)
Pedigree breeding and doubled haploid (DH) methods are the two widely used breeding approaches in maize by the International Maize and Wheat Improvement Center (CIMMYT) to derive fixed inbred lines. The objective of this study was to compare the variability and performance of testcross hybrids developed through pedigree and DH breeding methods from two breeding crosses. From each breeding cross, 40-45 fixed lines developed via pedigree and DH methods were used. The lines were crossed with a single cross tester from a complementary heterotic group, and the resulting testcrosses alongside the commercial checks were evaluated under optimum and stress conditions in Kenya, Tanzania and Uganda. The means and homogeneity of variances of grain yield and agronomic traits of the pedigree and DH lines were compared by using the Kolmogorov-Smirnov test. We found that the DH lines were distributed in the same manner as the pedigree lines for all traits under stress and optimum conditions. Both methods produced hybrids that were higher grain yielding than the best commercial checks included in the trials. Although the pedigree method had more opportunity for recombination than the DH method, our results indicated that it did not produce a sample of recombinants that differed significantly from the DH lines; thus, both methods were equally efficient for use in deriving homozygous lines from F1 hybrids. Both pedigree selection and DH breeding methods have their particular strengths and weaknesses, but neither is superior nor inferior in the development of inbred lines. However, the adoption of the DH method is increasing in large commercial maize breeding programmes due to faster production of genetically homozygous lines than the pedigree method.